2011
DOI: 10.1111/j.1365-246x.2011.04952.x
|View full text |Cite
|
Sign up to set email alerts
|

A benchmark study for glacial isostatic adjustment codes

Abstract: The study of glacial isostatic adjustment (GIA) is gaining an increasingly important role within the geophysical community. Understanding the response of the Earth to loading is crucial in various contexts, ranging from the interpretation of modern satellite geodetic measurements (e.g. GRACE and GOCE) to the projections of future sea level trends in response to climate change. Modern modelling approaches to GIA are based on various techniques that range from purely analytical formulations to fully numerical me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
153
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(160 citation statements)
references
References 110 publications
(168 reference statements)
7
153
0
Order By: Relevance
“…The other viscous amplitudes denoted by A i in Spada et al (2011) are shown to vanish identically. For Heaviside loading (f(s) = 1/s), the inverse Laplace transform of eq.…”
Section: Numerical Results For Polar Motionmentioning
confidence: 99%
See 4 more Smart Citations
“…The other viscous amplitudes denoted by A i in Spada et al (2011) are shown to vanish identically. For Heaviside loading (f(s) = 1/s), the inverse Laplace transform of eq.…”
Section: Numerical Results For Polar Motionmentioning
confidence: 99%
“…Under assumption (91), Vermeersen et al (1994), Sabadini & Vermeersen (2004) and Spada et al (2011) showed that the time relaxation of the polar motion m(t) is characterized only by the rotational frequencies a i . This fact is expressed by eq.…”
Section: Downloaded Frommentioning
confidence: 99%
See 3 more Smart Citations